Guidelines for Developing Schools into Educational Innovation Organizations Under the Office of Mahasarakham Primary Educational Service Area Office 2: - Pasacha, Sirikanya; Phoojomjit , Pongphop (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The development of educational institutions into innovation organizations is of utmost importance for ensuring high-quality education management. In this era of educational innovation, the new responsibilities of educational administrators require an augmented focus on innovation management to align with the advancements in the education sector. Therefore, this research aims to (1) study the current desirable state and the priority need of developing schools into educational innovation organizations under the office of Mahasarakham primary educational service area office. (2) Study the guidelines for developing schools into educational innovation organizations under the office of Mahasarakham primary educational service area office 2. Methodology: The research procedures were divided into two phases. The first stage was to study the current desirable state and the priority need of developing schools into educational innovation organizations, The sample group consisted of 306 school administrators and teachers, by stratified random sampling. The research instrument was a five-level questionnaire, with a reliability of 0.94. The statistics used for data were analyzed by mean, and standard deviation. The second stage was the study of the guidelines for developing schools into educational innovation organizations. The target groups include 3 schools for visiting best practices for studying the development guidelines and 9 experts for evaluating guidelines. The research instruments were interview form and evaluation form the suitability and feasibility. Results: The current state of developing schools into educational innovation organizations under the office of Mahasarakham Primary Educational Service Area office 2 overall was moderate level average and the desirable state overall was at the highest level. The priority needs ranked from high to low level were cooperation, 1) organizational culture 2) personnel development 3) innovative climate 4) organizational structure 5) strategic management. The guidelines for developing schools into educational innovation organizations, Include 1) principal 2) objectives 3) content 4) development 5) measurement and evaluation, Development content includes 5 modules: 1) organizational culture 2) personnel development 3)innovative climate 4) organizational structure 5) strategic management. The overall assess suitability and feasibility of the guidelines were at the highest level. Conclusion: The development of educational management into an innovation organization is crucial for the quality of school management and educational administration. This is because an innovation organization focuses on fostering innovation within the organization through proactive management, introducing new practices, and continuously developing and improving existing methodologies. Key components of this approach include organizational culture, personnel development, innovative climate, organizational structure, and strategic management.